1993
DOI: 10.1177/089686089301300311
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Magnesium Mass Transfer in Peritoneal Dialysis Patients Using 1.25 Mmol/L Calcium, 0.25 Mmol/L Magnesium Dialysis Fluid

Abstract: Objective To examine the effect of a reduced calcium/magnesium dialysis fluid (1.25/0.25 mmol/L, respectively) on calcium and magnesium mass transfer in both 1.36% and 3.86% glucose solutions. Design Each patient underwent four test exchanges, two with a standard dialysis fluid containing 1.36% and 3.86% glucose, and two with a reduced calcium/magnesium fluid containing 1.36% and 3.86% glucose. Calcium and magnesium were measured in dialysate and serum at ° and 240 minutes. Setting Single renal unit of a unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…As seen in earlier studies [ 24–28], the present study demonstrated a change from a positive to a negative calcium MT, when the calcium concentration in the dialysate was reduced from 1.75 to 1.25 mmol L −1 ( Fig. 4).…”
Section: Discussionsupporting
confidence: 89%
“…As seen in earlier studies [ 24–28], the present study demonstrated a change from a positive to a negative calcium MT, when the calcium concentration in the dialysate was reduced from 1.75 to 1.25 mmol L −1 ( Fig. 4).…”
Section: Discussionsupporting
confidence: 89%
“…For many years, PD solutions with a magnesium concentration of 0.75 mmol/L and calcium concentration of 1.75 mmol/L were used as ‘standard’ dialysate for the majority of patients although there has been a trend to lower dialysate calcium over the past decade. Patients using these solutions are slightly hypermagnesaemic [ 37 , 39 , 40 ] (see Table 1 ). This is because the transfer of magnesium is, if diffusive, mostly into the patient and thus positive [ 39 , 41 ].…”
Section: Magnesium In Dialysis Patientsmentioning
confidence: 99%
“…In contrast, when patients are treated with a low magnesium dialysate (0.25 mmol/L), serum magnesium levels normalize after some time, as dialytic magnesium balance is constantly negative, independent of glucose concentration, use of icodextrin (i.e. ultrafiltration) or treatment modality (continuous ambulatory PD or automated PD) [ 40 42 ] ( Table 1 ).…”
Section: Magnesium In Dialysis Patientsmentioning
confidence: 99%
“…Magnesium is predominantly an intracellular cation with an important role in cellular physiology. Serum levels are often slightly elevated in dialysis patients (Nilsson et al 1984) and are influenced by the concentration of dialysate magnesium (Hutchison et al 1993;Hutchison et al 1996). Retrospective studies suggest that magnesium may prevent vascular calcification in dialysis patients, although this remains controversial and has not been evaluated prospectively (Meema et al 1987).…”
Section: Mohammed and Hutchisonmentioning
confidence: 99%